Use of a Novel Anti-Infective Noble Metal Alloy-Coated Titanium Orthopedic Nail in Patients with Open Fractures: A Case Series from Malaysia - Thevarajan Karupiah; Aik Peng Yong; Ze Wee Ong; Heng Keat Tan; Wei Chern Tang; Hishamuddin Bin Salam (MDPI AG, 2022)
Fracture-related infection is a serious complication in orthopedic surgery with severe consequences for the patient. We evaluated whether a novel noble metal nail-coating technology can prevent bacterial adhesion and biofilm formation without interfering with bony union. In this retrospective, single-center case series, we described the incidence of fracture-related infections and bony union achievement in patients who had Gustilo type IIIa or IIIb femoral or tibial fractures treated with noble metal alloy-coated titanium nails. Patients were treated between January 2017 and January 2019 at the Sultanah Aminah Hospital, Johor Bahru, Malaysia. Information on fracture-related infections and bone healing assessments was collected from patient records. Additionally, three independent experts retrospectively reviewed patient X-ray images from follow-up visits to further evaluate bony union achievement. Thirty-five patients were included. Infection developed in 3/35 (8.6%) patients; all cases were resolved by antibiotic therapy. Radiographs were available for 32 patients; these confirmed the presence of bone healing in 30/32 (93.8%) patients. However, according to patient records, bony union was achieved in all patients. No safety issues were recorded. This case series suggests that a noble metal alloy-coated titanium nail can prevent infection and facilitate bony union achievement in patients undergoing surgery for severe open fractures.